The mechanism of dishabituation - Steiner, Genevieve Z.; Barry, Robert J. (Frontiers in Integrative Neuroscience, 2014)
The dual-process theory of habituation attributes dishabituation, an increase in responding to a habituated stimulus after an interpolated deviant, to sensitisation, a change in arousal. Our previous investigations into elicitation and habituation of the electrodermal Orienting Reflex (OR) showed that dishabituation is independent of sensitisation for indifferent stimuli, arguing against dual-process theory’s explanation. However, this could not be tested for significant stimuli in that study, because sensitisation was confounded with incomplete resolution of the preceding OR. This study aimed to clarify the mechanism of dishabituation for significant stimuli by extending the stimulus onset asynchrony (SOA) beyond the time required for the phasic response to resolve. Participants completed an auditory dishabituation task with a random SOA of 13-15 s while their electrodermal activity was recorded. The stimulus sequence was 10 standards, 1 deviant, 2-4 standards; counterbalanced innocuous tones. Two counterbalanced conditions were used: silently count all stimuli (significant) and no task (indifferent). Skin conductance responses (SCRs) and pre-stimulus skin conductance levels (SCLs) both decremented over trials 1-10. In both conditions, SCRs showed response recovery and dishabituation, indicating habituation, and post-deviant SCL sensitisation was apparent. Across all trials, phasic ORs were dependent on the pre-stimulus SCL (arousal level); this did not differ with condition. Importantly, dishabituation was independent of sensitisation for both conditions. Findings indicate that sensitisation, the change in state, is a process separate from phasic response resolution, and that arousal consistently predicts OR magnitude, including the dishabituation response. This argues against dual-process theory’s explanation, and instead suggests that dishabituation is a disruption of the habituation process, with magnitude determined by the current arousal level.